2017
DOI: 10.1186/s11689-017-9191-z
|View full text |Cite
|
Sign up to set email alerts
|

A resting EEG study of neocortical hyperexcitability and altered functional connectivity in fragile X syndrome

Abstract: BackgroundCortical hyperexcitability due to abnormal fast-spiking inhibitory interneuron function has been documented in fmr1 KO mice, a mouse model of the fragile X syndrome which is the most common single gene cause of autism and intellectual disability.MethodsWe collected resting state dense-array electroencephalography data from 21 fragile X syndrome (FXS) patients and 21 age-matched healthy participants.ResultsFXS patients exhibited greater gamma frequency band power, which was correlated with social and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
200
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(229 citation statements)
references
References 61 publications
28
200
1
Order By: Relevance
“…Rojas et al showed that tone‐evoked responses measured using magnetic fields are higher in the auditory cortex of individuals with FXS . EEG recordings revealed increased gamma frequency band power in resting state EEG of FXS patients . Auditory event related potential (ERP) studies report abnormally high amplitudes of the N1 wave in response to tones and reduced habituation to repeated sound in FXS .…”
Section: Fmrp Loss Alters Auditory Cortical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rojas et al showed that tone‐evoked responses measured using magnetic fields are higher in the auditory cortex of individuals with FXS . EEG recordings revealed increased gamma frequency band power in resting state EEG of FXS patients . Auditory event related potential (ERP) studies report abnormally high amplitudes of the N1 wave in response to tones and reduced habituation to repeated sound in FXS .…”
Section: Fmrp Loss Alters Auditory Cortical Activitymentioning
confidence: 99%
“…110 EEG recordings revealed increased gamma frequency band power in resting state EEG of FXS patients. 111 Auditory event related potential (ERP) studies report abnormally high amplitudes of the N1 wave in response to tones and reduced habituation to repeated sound in FXS. 110,[112][113][114][115] These data indicate a noisy resting state of auditory cortex in FXS that may lead to abnormal amplitude and synchronization of evoked responses.…”
Section: Auditory Cortical Activit Ymentioning
confidence: 99%
“…A large number of electrodes that are individually wired and connected with an external recording system quickly demands space on the animals head and this may be challenging. A solution can be found by the usage of multiplexed headstages: they overcome this limitation by combining the signals from many electrodes to a smaller number of connections directly on the animal's head (Wang et al, 2017).…”
Section: Eeg Electrode Implantsmentioning
confidence: 99%
“…Electroencephalography (EEG) analysis has revealed that FXS-affected individuals exhibit hyperexcitability in the neocortex and altered functional connectivity, suggesting impaired excitatory and inhibitory balance. [223][224][225][226] The Fmr1-KO mouse model enables cellular physiology analysis that is impossible in humans. Altered EEG has also been found in Fmr1-KO mice, and it has been used as a readout for pre-clinical assessment.…”
Section: Modeling Structural and Cellular Deficitsmentioning
confidence: 99%
“…For example, recent work has indicated that variability in behavior and cognition in FXS could be linked to variability in electrical activity in the brain of FXSaffected individuals, as measured by EEG. 223,336 One solution is the establishment of high-quality iPSCs from individuals with well-characterized and stratified clinical features. Stratification of affected individuals and cells could enable more effective linkage of disease characteristics with cellular phenotypes and better design of clinical trials.…”
Section: Challenges and Perspectives Clinical Variabilitymentioning
confidence: 99%